2002
DOI: 10.1007/bf03017409
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection by anesthetic agents against ischemia-reperfusion injury: An update for anesthesiologists

Abstract: P Pu ur rp po os se e: : The aim of this review of the literature was to evaluate the effectiveness of anesthetics in protecting the heart against myocardial ischemia-reperfusion injury.S So ou ur rc ce e: : Articles were obtained from the Medline database (1980-, search terms included heart, myocardium, coronary, ischemia, reperfusion injury, infarction, stunning, halothane, enflurane, desflurane, isoflurane, sevoflurane, opioid, morphine, fentanyl, alfentanil sufentanil, pentazocine, buprenorphine, barbitura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(135 citation statements)
references
References 134 publications
(235 reference statements)
0
126
0
5
Order By: Relevance
“…There is increasing evidence of anesthetic agent-induced protection. At present, isoflurane, sevoflurane and morphine appear to be most promising preconditioning-inducing agents 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence of anesthetic agent-induced protection. At present, isoflurane, sevoflurane and morphine appear to be most promising preconditioning-inducing agents 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on their potential benefits allows physicians to choose the best anesthetic or combination of anesthetics for their patients. It has been demonstrated that halogenated anesthetics, opioids, and propofol can protect against myocardial IRI 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, others suggested that myocardial norepinephrine levels were not increased by ischemic preconditioning in rabbits anesthetized with xylazine-ketamine, whereas they were increased in rabbits anesthetized with pentobarbital sodium (40) and that ketamine deactivates myocardial ATPsensitive potassium channels (35). Most investigators report that ketamine may attenuate preconditioning (24,33,(41)(42)(43). Isoflurane (13,56) and opioid agonists (23) have been shown to protect against ischemia-reperfusion injury and reduce IS.…”
Section: Limitationsmentioning
confidence: 99%
“…In studies I-III, it was intended to avoid volatile anaesthetics and propofol as both may have some cardioprotective properties (Kato 2002). Although ketamine may inhibit ischemic preconditioning (Molojavyi 2001), through inhibition of KATP channels, it was used for practical reasons for early anaesthesia induction, but not for maintenance.…”
Section: Anaesthesiamentioning
confidence: 99%
“…In combination with relatively high doses of fentanyl, which was not used in studies I-III, pancuronium may have a negative effect on myocardial lactate extraction (Gilbert 1990). The opioid fentanyl may have cardioprotective properties (Kato 2002), but probably in higher doses than were used in the studies I-III. Within the studies, the dosing regime was identical in all groups.…”
Section: Anaesthesiamentioning
confidence: 99%